PREDIKSI LAJU KOROSI DENGAN PERUBAHAN BESAR DERAJAT DEFORMASI PLASTIS DAN MEDIA PENGKOROSI PADA MATERIAL BAJA KARBON - Suriadi, IGA Kade; Suarsana, IK (Jurnal Energi Dan Manufaktur, 2012)
Abstrak Plastic deformation is metal forming process that resulted in material could not return as the initial condition both in its size and form. Plastic deformation process can be achieved by cold work i.e. metal forming processes below the cristalization temperature of the material. After cold work, the mechanical properties will change in its static, dynamic mechanical properties, and corrosive resistance. The experiment on the rate ofcorrosion was conducted in order to investigate the corrosion properties of the material. In this experiment, the setted up of deformation degree were 5%, 10%, 15%, and 20%, respectively. The material was low carbon steel AISI 3215. After treatment, each of samples was placed in corrosion mediums i.e. water, sea water, and air. The results showed that the average of corrosion rate in sea water increased from 0.0333 mm/year for the specimen with deformation degree 5% to 0.067 mm/year for specimen with deformation degree 20%. The rate of corrosion in water and air was lower than that of sea water.
Keywords: Deformation degree, heat treatment, corrosion rate